2007
DOI: 10.1562/0031-8655(2002)0750462ppaaao2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties and Antibacterial Activity of Meso-substituted Cationic Porphyrins¶

Abstract: A series of derivatives of 5,10,15,20‐tetrakis‐(4‐N‐methylpyridyl)‐porphine, where one N‐methyl group was replaced by a hydrocarbon chain ranging from C6 to C22, were characterized for their photophysical and photosensitizing properties. The absorption and fluorescence features of the various compounds in neutral aqueous solutions were typical of largely monomeric porphyrins, with the exception of the C22 derivative, which appeared to be extensively aggregated. This was confirmed by the very low triplet quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…3). Similar findings were observed by other authors, who obtained dark toxicity for the longer carbohydrate chain porphyrin derivatives (Reddi et al , 2002). The relatively long saturated alkyl chains (C>14) of the macromolecular ring can interact with hydrophobic areas in the cell membrane, inducing a marked alteration of the native three‐dimensional architecture and impairing specific metabolic processes and normal function of bacterial cells.…”
Section: Discussionsupporting
confidence: 92%
“…3). Similar findings were observed by other authors, who obtained dark toxicity for the longer carbohydrate chain porphyrin derivatives (Reddi et al , 2002). The relatively long saturated alkyl chains (C>14) of the macromolecular ring can interact with hydrophobic areas in the cell membrane, inducing a marked alteration of the native three‐dimensional architecture and impairing specific metabolic processes and normal function of bacterial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Also, it has been demonstrated that the efficiency of the inactivation of micro‐organisms by photosensitizers, namely of the porphyrinic type, is strongly dependent on structural features, such as charge number, charge distribution and amphiphilicity (Merchat et al. 1996; Reddi et al. 2002; Hamblin and Hasan 2004; Tomé et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that structural alterations consisting of the addition of positive charges and/or functional groups to a PS may increase its effectiveness in the inactivation of particular bacterial groups (Merchat et al. 1996; Reddi et al. 2002; Hamblin and Hasan 2004; Tomé et al.…”
Section: Introductionmentioning
confidence: 99%
“…Among the novel developed antibacterial agents, porphyrin complexes and their derivatives have attracted much attention due to their presence in natural systems which make them ideal candidates for use in medical applications [5][6][7]. Phthalocyanines differ from porphyrins by having nitrogen atoms link the individual pyrrol units.…”
Section: Introductionmentioning
confidence: 99%